Implementation of Governor's Regulation Number 35 of 2022 concerning the System and Procedure for the Disbursement of Funds at the South Sumatra Provincial Education Office - Maulina Maulina; Bukman Lian; Mahasir Mahasir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Governor's Regulation Number 35 of 2022 regulates the system and procedures for the disbursement of funds within the South Sumatra Provincial Government, including the Education Office. The implementation of this regulation aims to increase transparency, efficiency, and accountability in regional financial management. This study analyzes the extent to which these regulations have been implemented as well as the factors that affect their effectiveness. The research method used is qualitative descriptive with a case study approach at the South Sumatra Provincial Education Office. The results of the study show that the implementation of this regulation has had a positive impact in accelerating the process of disbursing funds and increasing budget supervision. However, there are still several obstacles, such as limited human resources who understand regulations and technical challenges in the financial administration system. Therefore, further training and improvement of financial system infrastructure are needed to optimize the implementation of this regulation.